Sustainability Analysis and Development Strategy for Catfish Cultivation in Tulungagung, East Java - Ambarwati, Widya; Yuliana, Ernik; Mudzakir, Abdul (JFMR (Journal of Fisheries and Marine Research), 2024)
Tulungagung Regency, located in East Java Province, is a region with significant fisheries potential, encompassing both marine capture and aquaculture. With 12,220 cultivators actively engaged in aquaculture, Tulungagung stands out as a key area for freshwater fish farming, particularly for species such as catfish, gourami, and tilapia. However, for these cultivators to succeed, it is crucial to assess the sustainability of their operations and develop effective business strategies. This research focuses on identifying the gaps in current cultivation practices and offering solutions to ensure both sustainability and profitability, especially in the catfish farming sector. Using a quantitative approach, the study surveyed 71 catfish cultivators across five prominent sub-districts in Tulungagung Regency. Data were gathered through observations and questionnaires distributed to the respondents in the January – April 2024 range. The sustainability of the catfish farming business was evaluated using a Likert scale, which assessed four key dimensions: technological, ecological, economic, and social. Additionally, a SWOT analysis was conducted to determine the most appropriate strategies for business development. The findings revealed that the combined index for the four sustainability dimensions was 72.78%, indicating that the catfish farming industry in Tulungagung Regency is relatively sustainable. The SWOT analysis positioned the business development strategy in quadrant II, suggesting a diversification approach that leverages the business's internal strengths to mitigate external threats.